ANALISIS RISIKO PRODUKTIVITAS TENAGA KERJA TERHADAP KINERJA WAKTU PROYEK PADA BANGUNAN BERTINGKAT - Rini, Indah Prasetiya; Tenriajeng, Andi Tenrisukki (Universitas Gunadarma, 2014)
Every construction project requires resources (resources) in the solution, namely labor, costs, tools, methods, and materials. Successful construction projects and whether or not depends on the effectiveness of resource management. In the process of achieving the project objectives, a predetermined limit, the greater the cost (budget) allocated, schedule, and quality that must be met. The third limitation is known by three constraints (triple constraint). By looking at the boundaries (triple constraint) specified in the project, especially the schedule to be met, labor productivity is very important in projects that affect the performance of a project. From the analysis using SPSS, obtained for the mathematical modeling of the relationship between labor productivity construction project time performance, ie Y = 125.518 - 2,044X16 - 3,406X6 - 2,422X15, where X16 is the placement of non-strategic materials, the X6 is a misunderstanding between labor and supervisors, and X15 is the lack of available tools, with the adjusted R-square of the regression equation reaches 0.784.Key words: regression analysis, project time performance, labor productivity.